Screening helper T lymphocyte epitopes based on IFN-γ/IL-10 ratio for developing a novel multi-epitope vaccine candidate using Wolbachia surface protein as an adjuvant against visceral leishmaniasis - Jianhui Zhang; Tianhang Lv; Shuoyan Tan; Lingqi Yu; Yangjian Chi; Jianping Chen; Xiaohui Fan; Xiaoyan Lu (Parasites & Vectors)
Abstract Background Visceral leishmaniasis (VL) is the most lethal form of leishmaniasis. In terms of anti-leishmanial vaccines, favorable immune responses are Th1 responses that primarily produce interferon gamma (IFN-γ) and activate macrophages for leishmanicidal effects. The selection of IFN-γ-inducing epitopes in silico may reduce the steps of pre-clinical evaluation and increase the certainty of the better-designed vaccine. Wolbachia surface protein (WSP) derived from Wolbachia bacteria that have been reported to reside in sandflies can trigger TLR2 and TLR4 activation to favor Th1 immune responses, which may serve as a potential adjuvant candidate for the Leishmania vaccine. Therefore, in this study, helper T lymphocyte epitopes that may induce favorable immune responses were identified, and WSP was served as an adjuvant to design a novel multi-epitope vaccine candidate. Methods Leishmania hemoglobin receptor (HbR), kinetoplastid membrane protein-11 (KMP-11), glycoprotein of 63 kDa (Gp63), thiol-specific antioxidant antigen (TSA), and sterol 24-c-methyltransferase (SMT) were analyzed by immunoinformatics to screen helper T lymphocyte and cytotoxic T lymphocyte epitopes. The antigenicity, toxicity, allergenicity, and IFN-γ-inducing epitope potential of T epitopes were predicted. The immune simulation was performed to calculate IFN-γ/interleukin (IL)-10 ratios to predict the immune responses induced by the helper T lymphocyte epitopes. Molecular docking and molecular dynamics simulations were carried out to analyze the interactions and stability of the docked complexes. The immune simulation of a multi-epitope vaccine candidate was carried out to predict its immunogenicity. Results Some helper T lymphocyte epitopes that were predicted with the potential of inducing Th1 responses and cytotoxic T lymphocyte epitopes were selected to develop a novel multi-epitope vaccine candidate with WSP as an adjuvant. It was found in molecular docking and interaction analysis that TLR2 and TLR4 can recognize WSP, supporting the potential of adjuvant for the Leishmania vaccine. The results from immune simulation demonstrated that the multi-epitope vaccine candidate induced obvious cytokine (IFN-γ, IL-12, and IL-2) secretion and Th1 as well as memory T cell production, similar to that of Leish-111f. Conclusions Our vaccine candidate may interact with TLR2 and TLR4 and exhibit good immunogenicity, favoring Leishmania clearance. Our strategy provides a novel multi-epitope vaccine candidate and references for other vaccine developments. Graphical Abstract